Functional disease architectures reveal unique biological role of transposable elements - Farhad Hormozdiari (Nature Portfolio, 2019)
Transposable elements (TE) make up a large component of the human genome and have been shown to contribute to human diseases. Here, Hormozdiari et al. estimate the contribution of TEs to the heritability of 41 complex traits and diseases and find enrichment of SINEs in blood traits.